Right heart dysfunction does not increase mortality associated with cemented hemiarthroplasty for hip fractures: A retrospective, preliminary analysis. - Atticus Coscia; Avnee Kumar; Michal Jandzinski; Lauren Swany; Francisco Fuster; Jaimo Ahn (PLoS ONE)
Background Cemented hemiarthroplasty (CH) is the preferred treatment for geriatric intracapsular hip fracture. Historically, there has been concern regarding cardiopulmonary morbidity related to bone cement impaction syndrome (BCIS). Right ventricular dysfunction predisposes to BCIS, though limited data supports this association. The purpose of this study was to evaluate if right heart dysfunction was predictive of mortality and cardiopulmonary morbidity following cemented hip hemiarthroplasty. Methods and findings This study was a retrospective chart review and analysis conducted at a tertiary referral medical center. Patients who underwent hemiarthroplasty (cemented or press fit) at a single institution for the treatment of intracapsular hip fracture between January 1, 2013, and January 1, 2021 and had an echocardiogram completed within 90 days of their surgery were retrospectively included. Two groups of patients with right heart dysfunction were evaluated: 1) patients who carried a preexisting diagnosis of pulmonary hypertension prior to hospital admission for hip hemiarthroplasty and, 2) patients with echocardiographic evidence of pulmonary hypertension. The primary outcomes included intraoperative hemodynamic instability consistent with bone cement impaction syndrome (BCIS), in-hospital mortality, and 1-year mortality. N = 74 patients were included. 45 patients underwent cemented hemiarthroplasty and 29 patients received press-fit stems. Preexisting diagnosis of right heart dysfunction and echocardiographic evidence of right heart dysfunction were not significantly associated with BCIS, in-hospital, nor 1-year mortality. However, cementation was significantly associated with 1-year mortality (p < 0.05). Conclusions Right heart dysfunction does not appear to predispose patients to cardiopulmonary complications or early mortality following cemented hip hemiarthroplasty. Cementation was, however, independently associated with 1-year post-operative mortality. These data add to a growing body of literature which suggests that patients with multiple medical comorbidities may be at risk of adverse outcomes related to cementation. BCIS is uncommon, remains poorly understood, and further investigation is warranted.